ANALISIS PENGGUNAAN BANDWIDTH MANAGEMENT MENGGUNAKAN SECURE SERVICE GATEWAY UNTUK MENGATUR KECEPATAN TRANSMISI DATA (Studi Kasus : PT. Mitra Servisindo Utama) - Sadidan Muqorobin; Hadi Zakari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
PT. Mitra Servisindo Utama is a company engaged in information technology consulting services with work areas covering several areas within the city and outside the city. In this company there are many users who access the internet without any limitations in bandwidth usage, so that there are obstacles to the performance of the internet network being less stable. To overcome excessive and uncontrolled bandwidth usage that causes disruption of the company's internet network connection, in this case the researcher can solve it by using Secure Service Gateway (SSG) hardware with the Network Development Life Cycle (NDLC) method in order to help organize and manage bandwidth usage as well as assisting the development of the company's computer network. In the results of this study, it is hoped that the Secure Service Gateway (SSG) hardware with the Network Development Life Cycle (NDLC) method can produce more controlled bandwidth usage and more optimal computer network connections.